Characteristics of polyps in Lebanese population - Antoine Abou Rached; Joyce Sanyour; Jowana Saba; Melissa Abou Khalil; Rasha Matar; Pierre Khalil; Saad Khairallah (International Journal of Medical Research and Review, 2023)
Background:The objective of this study is to describe characteristics of the polyps in Lebanese population and evaluate the dysplasia and its relation to the polyps’ locations.Methods: Retrospective descriptive study was conducted at the Department of National Institute of Pathology in Lebanon and comprised biopsy of colonic polyps or resected polyps from patients from 2007 to 2009. We collected demographic data and polyps’ characteristics. Then, we divided patients according to age sex, location, histology.Results: With 2298 polyps in 1470 patients, the mean age was 57.45 with 68% aged more than 50yo. 75.6% have one polyps and multiple polyps more commonly found in older patient (> 50 years). More than 20 % of polyps found in the recto-sigmoid area. In the right colon, people older than 50 years were more likely to have polyps (19%) compared to those < 30 years (8.3%) (p < 0.05). In the rectum, people < 30 years were more likely to have polyps compared to those > 50 years (p < 0.01). Concerning the histology, tubular adenoma is the most common type and more prevalent in left colon. Hyperplastic polyps mainly found in the recto-sigmoid area and mainly in age group 30-50 in contrast to adenomatous polyps found over 50yo. Adenocarcinomas and/or degenerative polyps were founded in 5.9% of our population.Conclusion:This study gives valuable information on colorectal polyp in Lebanese population about age, sex, dominant histology and anatomic location. We noted a male predominance and mainly above 50 years old. The majority had single polyps, >50% of polyps were localized in the recto sigmoid. Adenomatous polyps were the most common type.